(untitled) (Clinics, 2013)
OBJECTIVES: Both renal function and immune system function decline with age. Although controversial, a significant number of studies have shown that the decline in kidney function is associated with the worsening of the immune system. These findings are reinforced by the increased susceptibility to infections and deficient immunization coverage after vaccination both in patients with chronic renal disease and in elderly individuals. Our objective was to evaluate a non-institutionalized elderly population from São Paulo City and correlate the estimated glomerular filtration rate with the percentage of lymphocytes in circulation. METHODS: A random population of 237 individuals (107 men and 130 women), ranging in age from 60 to 101 years, who were enrolled in the Health, Well-Being and Aging Study was evaluated for renal function (Modification on Diet in Renal Disease formula) and lymphocyte percentage (flow cytometry). RESULTS: Aging was associated with a decrease in the estimated glomerular filtration rate in both male and female individuals. We did not identify a significant correlation between the estimated glomerular filtration rate and either the percentage of CD4, CD8, and B cells or CD4/CD8 ratio. The median percentage of CD8+ T cells was significantly lower in individuals with an estimated glomerular filtration rate >;60 mL/min/1.73 m². CONCLUSIONS: In this study, no statistical correlation was found between the estimated glomerular filtration rate and either the lymphocyte phenotype (CD4+,CD8+, and CD19+ cells) or the CD4/CD8 ratio in blood.